Maximizing Tendencies in Marriage: Accentuating the Implications of Readily Observable Partner Characteristics for Intimates' Satisfaction. (October 2019) - French, Juliana E.; Meltzer, Andrea L.
People differ in their tendencies to labor over decisions and to make choices that maximize their outcomes—a difference known as maximization. Here, we used two independent, 3-year longitudinal studies of newlywed couples to demonstrate that this individual difference in decision making has important implications for romantic relationships. Consistent with the idea that maximizers are more likely to compare their current romantic partners to potential alternative partners' readily observable qualities, such as their physical attractiveness and status, results demonstrated that intimates' maximization moderated the implications of these sex-differentiated variables for marital satisfaction. Specifically, maximizing men who had attractive (vs. unattractive) wives were more satisfied at the start of their marriages. Likewise, maximizing women who had high (vs. low) status husbands experienced less steep declines in satisfaction over time. These findings demonstrate that maximization has important implications for long-term romantic relationships by accentuating the effects of readily observable partner qualities on relationship outcomes.